Sexual regulation and the law : a Canadian perspective - Jochelson, Richard, 1973-; Gacek, James (Demeter Press, 2019)
"Does Canada need any more collections about legal regulation of sex and sexuality? Volumes exist dealing with sex work and pornographies. Certainly, volumes abound dealing with emerging sexualities in Canada and new sexual freedoms. This book seeks to do more than tell a story of broad generalities about the law. It forges the links between the history of law and modern iterations of judgments pertaining to that law. Hence the uncomfortable line between Victorian morality (often) and modern regulation, is thematically explored through the book. More modern iterations of sexual regulation in Canada are being deployed and, in this book, the authors explore the interplay between emerging digital technologies and legal regulation. Newer laws in Canada have been drafted to recognize that sexual expression can be a means of violence inherently, and thus an exploration of modern sexual digital expression and its emerging jurisprudence represent a new frontier in the regulation of sex and sexuality in Canada. We explore how legal regulation has responded to these new crimes."--